Individual and Contextual Characteristics Associated With Alcohol Use Among Brazilian Adolescents - Patrycia Sarah Martins Arruda; Aline Natália Silva; Ana Elisa Madalena Rinaldi; Luciana Saraiva da Silva; Catarina Machado Azeredo (Frontiers Media S.A., 2022)
Objective: To analyze the association between individual and contextual characteristics with alcohol indicators of experimentation, use in the last 30 days and drunkenness in Brazilian adolescents.Methods: Cross-sectional study based on data from 100,914 student attending 9th grade from the 2015 National School Health Survey. Multilevel logistic regression models were performed for the outcomes: alcohol experimentation; use in the last 30 days and drunkenness; and exposures, adjusted for adolescents' sociodemographic characteristics.Results: Girls were more likely to experiment alcohol (OR = 1.09; 95% CI = 1.05-1.12), use it in the last 30 days (OR = 1.09; 95% CI = 1.00-1.13) and less prone to drunkenness (OR = 0.90; 95% CI = 0.87-0.93). A higher proportion of public-school students reported drinking. There was a positive association of substance use by parents, peers and the adolescents themselves with the outcomes. Having a policy of banning alcohol consumption at school was associated with a greater chance of alcohol experimentation in public schools.Conclusion: Exposure to legal and illegal substances by friends, family members and a prohibitive school environment favored the outcomes.